Multi-beam Sonar Signal Simulation and Field Programmable Gate Array Implementation - Luo, Yu; Li, Shiwen; Shi, Jian; Cheng, Mengdi (Journal of physics. Conference series, 2023)
The multi-beam bathymetric sonar system is one of the top pieces of equipment for ocean exploration. The action distance of multi-beam bathymetric sonar depends on the pulse width of the signal, and the distance resolution depends on the bandwidth of the transmitted signal. In this paper, a chirp signal generation method for shallow water multibeam sonar based on FPGA is presented to improve the performance of multibeam bathymetric sonar. A chirp signal is generated using a hardware description language with a bandwidth of B = 50 kHz and a pulse width of T = 1 ms. Compared with the traditional look-up table method, this method could release plenty of hardware resources.